A probabilistic study of brittle failure in dowel-type timber connections with steel plates loaded parallel to the grain. Issue 5 (3rd September 2019) - Cabrero, José Manuel; Honfi, Dániel; Jockwer, Robert; Yurrita, Miguel
ABSTRACT: Dowel-type connections in timber structures should be typically designed in a way that, if the load bearing capacity is exceeded, desirable ductile failure should likely occur, i.e. yielding of the metal dowel or embedment of the timber. However, the probability of brittle failures cannot be completely avoided in many cases. If the connection is loaded parallel to the grain direction, splitting, row-shear, plug/block shear and tensile failure are examples of such brittle failure modes. To ensure a beneficial structural performance locally and sufficient structural robustness globally, the probability of such brittle failures should be kept at a sufficiently low level. However, in the current version of EN1995, the probability of such failure is not considered explicitly. The final aim of the presented research study is to develop a rational approach for the consideration of brittle failure in timber connections with dowel-type fasteners and steel plates loaded parallel to the grain, consistently with the partial factor method. As a first step, a probabilistic model has been used to study the susceptibility to brittle failure and provide a rational basis for the calibration of a "brittle overstrength factor". The results of this study are reported in the current contribution.